Acute phase protein responses in mice infected with river water contaminated by Pasteurella multocida type B: 2 - Khaleel, Mohammed Muqdad; Abdullah, Faez Firdaus Jesse; Adamu, Lawan; Osman, Abdinasir Yusuf; Haron, Abd Wahid; Saad, Mohd Zamri; Omar, Abdul Rahman (Science Publications, 2013)
Animals are predisposed to infections through varieties of ways which activate the innate immune systems at the initial phase of acute infections. Hemorrhagic Septicemia (HS) is a devastating septicemic disease of cattle and buffaloes caused by a particular serotypes of Pasteurella multocida and serotype B: 2 is the most important cause of the disease in Asia. Therefore, the present study aims to investigate on acute phase protein responses in mice infected with river water contaminated by Pasteurella multocida type B: 2. Five infected mice were placed in each tank containing river water for 24, 48 and 72 h. The groups comprise of five mice each made up of the control, intraperitoneal, oral and the aerosol routes. There were increased concentrations of Haptoglobin (Hp) in the mice inoculated with infected river water kept for 24 h intraperitoneally (p<0.0454) relative to the control, oral and the aerosol routes. There was significant increased concentration of Serum Amyloid A (SAA) in the mice that were inoculated with infected river water kept for 72 h intraperitoneally (p<0.0020) compared to control, orally and the aerosol routes. The intraperitoneal route though most effective in response but practically not feasible for vaccine administration in larger animals and the oral routes was inadequate in eliciting acute phase response in the present study of mice model. Therefore, the aerosol routes could perhaps be a readily available route for effective vaccine administration and heightened immunity in animals considering the progressive responses of APPs through this route.